The mis-measurement of extreme global poverty: A case study in the Pacific Islands. (September 2015) - Deeming, Christopher; Gubhaju, Bina
Debate over the measurement of global poverty in low- and middle-income countries continues unabated. There is considerable controversy surrounding the 'dollar a day' measure used to monitor progress against the Millennium Development Goals. This article shines fresh light on the debate with new empirical analyses of poverty (including child poverty), inequality and deprivation levels in the Pacific island state of Vanuatu. The study focuses not only on economic and monetary metrics and measures, but also the measures of deprivation derived from sociology in relation to shelter, sanitation, water, information, nutrition, health and education. Until recently, there had been few, if any, attempts to study poverty and deprivation disparities among children in this part of the world. Different measures yield strikingly different estimates of poverty. The article, therefore, attempts to situate the study findings in the broader international context of poverty measurement and discusses their implications for future research and the post-2015 development agenda.